The Swollen Knee - Levy, David R. (1983)
Family physicians are often confronted by a patient with a swollen knee. It is important to realize that swelling is a sign, not a diagnosis. An organized clinical examination includes eliciting a detailed history; inspection (comparing the swollen knee to the other); palpation (testing for fluid, ligamental stability and meniscal injury). Such an examination, coupled with knowledge of the causes and effects of various knee effusions, allows the physicians to embark on a therapeutic and diagnostic treatment program. By understanding the consequences of the problem, the physician is already on his way to finding a solution that will be gratifying both to him and to his patient. Treatment may include early aspiration of the effusion and/or seeking a consultant's opinion.